SELF-MANAGEMENT TOOLS FOR OPTIMIZING THE WORKING PROCESS IN ORGANIZATIONS (Development Service Industry Management, 2024)
Self-management is an important tool for optimizing the workflow in organizations, as it allows employees to effectively manage their time, resources and tasks. It is noted that the successful use of self-management methods helps to increase productivity, improve the quality of work performed, and reduce the level of stress, which, in turn, positively affects the overall effectiveness of the organization. The main tools that can be implemented to improve work processes at the individual and collective levels are considered. It is emphasized that one of the key aspects of self-management is time management, which includes planning tasks, determining priorities and meeting deadlines. This allows employees to avoid overload and ensures a more rational use of working time. Effective time management also helps maintain work-life balance, which is an important factor in maintaining long-term motivation and preventing professional burnout. It is noted that another important element of self-management is task management. The use of tools such as to-do lists, digital planners and project management systems allows you to better organize the workflow and ensure timely completion of tasks. In addition, self-management involves the development of skills to control one's own attention and energy. This includes concentration techniques and regular rest breaks to help maintain a high level of productivity throughout the day. Understanding one's own energy cycles allows employees to plan their work more effectively, completing the most complex tasks during peak activity periods. In general, self-management tools can significantly improve the work process in organizations, helping to increase productivity, reduce stress and improve overall job satisfaction. Implementing these practices at the individual and team levels allows organizations to more effectively achieve their strategic goals while creating an environment conducive to professional development and personal growth of employees.
Keywords: self-management; work process optimization; time management; productivity; task management; adaptability; professional development; organizational effectiveness